Effect of the Alkalized Rice Straw Content on Strength Properties and Microstructure of Cemented Tailings Backfill - Wang, Shi; Song, Xuepeng; Wei, Meiliang; Liu, Wu; Wang, Xiaojun; Ke, Yuxian; Tao, Tiejun (Frontiers in Materials, 2021)
The tailings and rice straw are waste by-products, and the storage of tailings on the ground and the burning of rice straws will seriously damage the ecological environment. In this study, the effect of different contents of alkalized rice straw (ARS; rice straw was alkalized with 4% NaOH solution) on the mechanical properties and microstructure of cemented tailings backfill (CTB; ARSCTB) was studied through uniaxial compressive strength (UCS), scanning electron microscopy (SEM), and X-ray diffraction (XRD) tests. The results indicated that 1) the UCS of ARSCTB could be improved by ARS. However, with the increase in the ARS content from 0.1 to 0.4 wt%, the UCS showed a monotonous decreasing trend. The UCS improvement effect was best when the ARS content was 0.1 wt%, and at 7, 14, and 28 days curing ages, the UCS increased rate was 6.0, 8.3, 14.7% respectively. 2) The tensile strength of ARSCTB was generally higher than that of CTB and positively correlated with the ARS content. The tensile strength increase rate was 24.1–34.2% at 28 days curing age. 3) The SEM test indicated that the ARS was wrapped by cement hydration products, which improves its connection with the ARSCTB matrix. ARS performed a bridging role, inhibited cracks propagation, and provided drag or pulling force for the block that is about to fall off. Therefore, the mechanical properties of ARSCTB were enhanced. However, under high ARS content, the inhibition of ARS on hydration reaction and the overlap between ARS were not conducive to the improvement of the UCS of ARSCTB. 4) The post-peak residual strength and integrity effect of ARSCTB were greater. It is recommended to add 0.1–0.2 wt% ARS to the backfill with high compressive strength requirements such as the empty field subsequent filling mining method and the artificial pillar. 0.3–0.4 wt% ARS is incorporated into backfill with high tensile strength requirements such as high-stage filling with lateral exposure and artificial roof. This study further makes up for the blank of the application of plant fiber in the field of mine filling and helps to improve the mechanical properties of backfill through low-cost materials.